Das Produktionspotential in Ostdeutschland - Thomas Westermann (Deutsche Bundesbank, 1995)
Potential output is an elusive concept. This stands in sharp contrast to its prominent role in economic analysis. In particular, monetary targetting as practised by the Deutsche Bundesbank relies on an estimate of future potential output growth. Different approaches usually lead to fairly similar results in the case of deep-rooted and evenly developing market economies such as West Germany. In this paper we have a stab at estimating potential output for East Germany since unification in mid-1990, using some variants of these techniques. As will be shown, the results can so far not be reconciled with stylized outcomes such as a low variance of growth rates and output gaps that by and large average out over the sampie period ...
Keywords: 330; Produktionspotenzial; Wirtschaftliche Anpassung; Schätztheorie; Neue Bundesländer